2007
DOI: 10.1159/000098707
|View full text |Cite
|
Sign up to set email alerts
|

Age at Growth Hormone Therapy Start and First-Year Responsiveness to Growth Hormone Are Major Determinants of Height Outcome in Idiopathic Short Stature

Abstract: Aim: To develop methods to identify factors associated with a favorable outcome in GH-treated children with idiopathic short stature (ISS). Methods: From 4,685 children listed as having ISS within KIGS (Pfizer International Growth Database), we studied (a) the prediction model group (n = 657) to develop the first-year prediction model, and (b) the near adult height group (NAH; n = 256) which received GH for >4 years to develop descriptive models for adult height and overall height gain. Results: NAH group at G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
94
3
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 85 publications
9
94
3
2
Order By: Relevance
“…Compared to our data in patients with SHOX deficiency, prediction of growth response in GH deficiency seems to be more accurate [21][22][23]. Based on the fact that the growth response in the first year is associated with the long-term outcome, it is reasonable to evaluate the growth response as early as possible to predict the long-term outcome [28][29][30]. Although the experience with GH therapy over 30 years suggests that GH treatment is safe [31,32], discussions about adverse effects especially in the long-term flared up again recently because of results from the French cohort of the Safety and Appropriateness of Growth Hormone Treatments in Europe (SAGhE) study [33,34].…”
Section: Discussionmentioning
confidence: 62%
“…Compared to our data in patients with SHOX deficiency, prediction of growth response in GH deficiency seems to be more accurate [21][22][23]. Based on the fact that the growth response in the first year is associated with the long-term outcome, it is reasonable to evaluate the growth response as early as possible to predict the long-term outcome [28][29][30]. Although the experience with GH therapy over 30 years suggests that GH treatment is safe [31,32], discussions about adverse effects especially in the long-term flared up again recently because of results from the French cohort of the Safety and Appropriateness of Growth Hormone Treatments in Europe (SAGhE) study [33,34].…”
Section: Discussionmentioning
confidence: 62%
“…Several studies have demonstrated that growth response on GH treatment is positively influenced by a young age at the start of treatment (Ranke et al 2007). Moreover, optimal long-term outcome, such as stature, in inherited disorders depends on early diagnosis and good metabolic control (MaCdonald et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Generally growth data after one year of treatment with recombinant GH are regarded significant for the response to therapy also during the following years and for the final height outcome [11][12][13][14][15][16][17][18][19]. For our whole group of NSD-patients we found a mean gain of H-SDS of 0,77 ± 0,48, HV almost doubled (8,24 ± 1,58 cm/year versus 4,32 ± 1,68 cm/year at baseline) and HV-SDS increased by 4,40 ± 3,5.…”
Section: Igf-i-and Igfbp3 After 3 Months and Growth Response After 12mentioning
confidence: 99%